2023
DOI: 10.3390/ma16155223
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Al-Si Alloys Produced by Rapid Solidification and Hot Extrusion

Abstract: The paper presents the results of tests of rapid solidification (RS) aluminum alloys with the addition of silicon (5%, 11%, and 20%). Casting by melt-spinning on the surface of an intensively cooled copper cylinder allowed to obtain a metallic material in the form of flakes, which were then consolidated in the process of pressing and direct extrusion. The effect of refinement on structural components after rapid solidification was determined. Rapidly solidified AlSi materials are characterized by a comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The higher elongation in the case of plastically consolidated materials (curves B and C) compared to the gravity cast material (curve A) is caused by the presence of large areas of the plastic matrix, which can be seen in Figure 5. Similar research results can be found in the literature [36,52].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The higher elongation in the case of plastically consolidated materials (curves B and C) compared to the gravity cast material (curve A) is caused by the presence of large areas of the plastic matrix, which can be seen in Figure 5. Similar research results can be found in the literature [36,52].…”
Section: Resultssupporting
confidence: 92%
“…In the case of components such as chips, this is more problematic, due to the fact that after machining processes, chips are often contaminated with coolant and their surface oxidizes quickly, which causes a decrease in the efficiency of the melting process. Remelting the chip after the machining process, such as cutting, turning, or milling, is very unprofitable because, at the end of the process, we will have achieved only 40% of the input material mass, to obtain up to 100% of the mass of the finished product, compared to the mass of the input material [35,36].…”
Section: Raw Materialsmentioning
confidence: 99%
“…The analysis also shows how higher values of Kts lead to lower values for the Equation (30) terms, as the influence of Kts on the model variables is reduced. In conclusion, the terms a•(rCE1) 4 , b•(rCE1) 3 , and e•(rCE1) are approximated to zero.…”
Section: Application Of the Analytical Modelmentioning
confidence: 93%
“…Aluminum alloys have broad potential for applications in aerospace, automotive, defense, electronics, and biomedical industries, but the performances of parts produced by the traditional casting process are poor [ 2 ]. Traditional casting and its low cooling rates cause macro-segregation and coarse structures in aluminum alloys [ 3 ]. To overcome this issue, together with the need for a long production chain and the limited flexibility of plastic processing, numerous studies on AM can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum owes this place to a set of properties which, in many circumstances, make it an irreplaceable material. During their use, metals change from a liquid to a solid state [1][2][3][4][5][6]. Additionally, the solidification of any metal or alloy can be studied by thermal analysis.…”
Section: Introductionmentioning
confidence: 99%